2015
DOI: 10.3171/2014.9.jns132791
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopically assisted ventriculoperitoneal shunt placement: a prospective randomized controlled trial

Abstract: OBJECT In ventriculoperitoneal (VP) shunt surgery, laparoscopic assistance can be used for placement of the peritoneal catheter. Until now, the efficacy of laparoscopic shunt placement has been investigated only in retrospective and nonrandomized prospective studies, which have reported decreased distal shunt dysfunction rates in patients undergoing laparascopic placement compared with mini-laparotomy cohorts. In this randomized controlled trial the authors compared rates of shunt failure in patients who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 30 publications
1
41
0
Order By: Relevance
“…Since 2014, the abdominal shunt placement is performed by a visceral surgeon using the laparoscopic technique. 12 Patients from the freehand cohort operated on before 2014 underwent a mini-laparotomy for abdominal VPS placement done by a neurosurgeon .The "Kocher entry point" (measured at 11-12 cm from the nasion and 3-3.5 cm lateral to the midline) was used as the frontal entry point. The "trigonum entry point" (measured at 4 cm behind and 5.5 cm above the external auditory canal) was used as the occipital entry point.…”
Section: Operative Techniquementioning
confidence: 99%
“…Since 2014, the abdominal shunt placement is performed by a visceral surgeon using the laparoscopic technique. 12 Patients from the freehand cohort operated on before 2014 underwent a mini-laparotomy for abdominal VPS placement done by a neurosurgeon .The "Kocher entry point" (measured at 11-12 cm from the nasion and 3-3.5 cm lateral to the midline) was used as the frontal entry point. The "trigonum entry point" (measured at 4 cm behind and 5.5 cm above the external auditory canal) was used as the occipital entry point.…”
Section: Operative Techniquementioning
confidence: 99%
“…Current VP shunt failure rates in adult patients still approach 15%-20% in the 1st year after treatment with first failure and repeat surgery occurring within 6-12 months. 21,22,30 In addition, longterm follow-up of shunt-treated patients demonstrated continued significant risk of shunt failure requiring repeat surgeries.…”
Section: Long-term Etv Treatment Outcomesmentioning
confidence: 99%
“…A recent randomized trial in adult patients suggested that laparoscopic placement of the distal catheter led to less distal failures compared with minilaparotomy, although the overall shunt failure rate was no different between the 2 groups. 28 We are currently attempting to quantify and define what we term the Preventable Shunt Revision Rate (PSRR) as a potential shunt surgery measure. Revision shunt surgery performed because of a malpositioned proximal catheter (e.g., a hole-bearing region of the catheter completely within parenchyma) or distal catheter (e.g., preperitoneal placement), or shunt components that were not properly assembled or secured are examples of errors in surgical technique that could be prevented.…”
Section: Implications Of the Findingsmentioning
confidence: 99%